Monitoring swim training based on mean intensity strain and individual stress reaction of an elite swimmer - Ungerechts, B. E.; Steffen, R.; Vogel, K. (Biomechanics and Medicine in Swimming XI, 2010)
Swim coaches prescribe training to enhance the properties required for a person to swim the same distance in less time. Monitoring training strain may give a clue to the relationship between training and race performance. Mujika (1996) monitored a training season reducing training components to one MITS-value (mean intensity of a training season). Since training strain is modulated by personal traits into an internal fatiguing impulse, cooperation by the athlete is essential to monitor the perceived stress at the end of a day and the next morning, respectively. The difference of both items, called delayed perceived fatigue, and MITS-value of a world level female swimmer was registered for 144 days: MITS = 2.01 ± 0.12 and the delayed perceived fatigue = -1.31 ± 1.81 arbitrary units, respectively. The increase of the race performance was 2.8%.